Edmund Clarence Stedman papers - Stedman, Edmund Clarence, 1833-1908.
Correspondence, poems, and other papers. Correspondents include Edward Howard House.
Poet, editor, drama critic, and banker.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: House, Edward Howard, -- 1836-1901 -- Correspondence; American poetry; American literature; Bankers; Critics; Editors; Poets